Efficacy of non‐invasive mechanical ventilation in the general ward in patients with chronic obstructive pulmonary disease admitted for hypercapnic acute respiratory failure and pH < 7.35: a feasibility pilot study. Issue 5 (May 2015) - Fiorino, S.; Bacchi‐Reggiani, L.; Detotto, E.; Battilana, M.; Borghi, E.; Denitto, C.; Dickmans, C.; Facchini, B.; Moretti, R.; Parini, S.; Testi, M.; Zamboni, A.; et al.
Abstract Aim To date non‐invasive (NIV) mechanical ventilation use is not recommended in chronic obstructive pulmonary disease (COPD) patients with acute respiratory failure (ARF) and pH < 7.30 outside a 'protected environment'. We assessed NIV efficacy and feasibility in improving arterial blood gases (ABG) and in‐hospital outcome in patients with ARF and severe respiratory acidosis (RA) admitted to an experienced rural medical ward. Methods This paper is a prospective pilot cohort study conducted in the General Medicine Ward of Budrio's District Hospital. Two hundred and seventy‐two patients with ARF were admitted to our Department, 112, meeting predefined inclusion criteria (pH < 7.35, PaCO2 > 45 mmHg). Patients were divided according to the severity of acidosis into: group A (pH < 7.26), group B (7.26 ≤ pH < 7.30) and group C (7.30 ≤ pH < 7.35). ABG were assessed at admission, at 2–6 h, 24 h, 48 h and at discharge. Results Group A included 55 patients (24 men, mean age: 80.8 ± 8.3 years), group B 31 (12 men, mean age: 80.3 ± 9.4 years) and group C 26 (15 men, mean age: 78.6 ± 9.9 years). ABG improved within the first hours in 92/112 (82%) patients, who were all successfully discharged. Eighteen per cent (20/112) of the patients died during the hospital stay, no significant difference emerged in mortality rate (MR) within the groups (23%, 16% and 8%, for groups A, B and C, respectively) and between patients with or without pneumonia: 8/29 (27%) versus 12/83 (14%). On multivariable analysis, only age and Glasgow Coma Scale had an impact on the clinical outcome. Conclusion In a non‐'highly protected' environment such as an experienced medical ward of a rural hospital, NIV is effective not only in patients with mild, but also with severe forms of RA. MR did not vary according to the level of initial pH.